2015
DOI: 10.1136/emermed-2014-204388
|View full text |Cite
|
Sign up to set email alerts
|

The impact of senior doctor assessment at triage on emergency department performance measures: systematic review and meta-analysis of comparative studies

Abstract: This review demonstrates that SDT can be an effective measure to enhance ED performance, although cost versus benefit analysis is needed. The potential high risk of bias in the evidence identified, however, mandates more robust multicentred studies to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 43 publications
(110 reference statements)
3
62
0
1
Order By: Relevance
“…Both of these studies occurred in Canada, however, where delivery care might be diferent than other setings, thus limiting their generalizability [51,52]. Two other randomized controlled trials demonstrated no afect of physician in triage on LOS [50].…”
Section: Improving Emergency Department Patient Throughputmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these studies occurred in Canada, however, where delivery care might be diferent than other setings, thus limiting their generalizability [51,52]. Two other randomized controlled trials demonstrated no afect of physician in triage on LOS [50].…”
Section: Improving Emergency Department Patient Throughputmentioning
confidence: 99%
“…A systemic review of triage nurses ordering radiographs has demonstrated nearly a 20-min decrease in patient LOS with implementation of triage nursing orders [49]. Studies have suggested that having an advanced practitioner or a physician in triage may reduce the ED LOS and rates of leaving without being seen [45,50]. Two randomized trials of physician in triage demonstrated reduced patient LOS by 36 min in one study (12% reduction) [51], and 122 min in the other (35% reduction) [52].…”
Section: Improving Emergency Department Patient Throughputmentioning
confidence: 99%
“…Triage liaison physicians were reported to have had an impact in reducing ED lengths of stay, compared with nurse-led triage, 219 and senior doctor triage could reduce both waiting times and length of stay in the ED. 204 Three reviews assessed the evidence on use of observation or assessment units and short-stay wards. One concluded that assessment or observation units had potential to produce benefits, including facilitating early senior clinician involvement and reducing length of stay and inappropriate admissions, but that this may only apply to specific diagnostic groups.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…In the absence of a risk of bias assessment, it is more difficult to assess the strength of the evidence underlying the review's conclusions. Seventeen reviews 204,205,[207][208][209][210][211][212][213][215][216][217][218][219][220]222,224 were judged to have used an appropriate method to synthesise the studies. In most cases a narrative approach was used because the included studies were too heterogeneous for meta-analysis.…”
Section: Qualitymentioning
confidence: 99%
See 1 more Smart Citation